Adjective Reduplication of Sasak Dialect Meno-Mene in Karang Bagu - Nursaly, Baiq Rismarini (VELES Voices of English Language Education Society, 2019)
This research aims to describe forms and types of adjective of Sasak dialect Meno-Mene that is spoken in Lingkungan Karang Bagu, Karang Taliwang Subdistrict, Mataram City, West Nusa Tenggara Province. Word reduplication in a language is included in structural study of morphology. According to Verhaar (1988:52) in his book Pengantar Linguistik, morphology is a part of linguistics that studies grammatical arrangement of parts of word. Data in this research comes from utterances spoken by Sasak speakers in Lingkungan Karang Bagu. Data collection was done by using observation and interview technique. The collected data were analyzed using intralingual identity method. Result of analysis shows that the morphological process of adjective reduplication of Sasak dialect Meno-Mene in Karang Bagu was divided into 4 based on: basic word form, reduplication form, reduplication function, and reduplication meaning.